Solmap: Project In India's Solar Resource Assessment - Mitra, Indradip; Chhatbar, Kaushal; Kumar, Ashvini; Giridhar, Godugunur; Vashistha, Ramdhan; Meyer, Richard; Schwandt, Marko (International Journal of Renewable Energy Development, 2014)
India launched Jawaharlal Nehru National Solar Mission in 2009, which aims to set up 20 000 MW of grid connected solar power, besides 2 000 MW equivalent of off-grid applications and cumulative growth of solar thermal collector area to 20 million m2 by 2022. Availability of reliable and accurate solar radiation data is crucial to achieve the targets. As a result of this initiative, Ministry of New and Renewable Energy (MNRE) of Government of India (GoI) has awarded a project to Centre for Wind Energy Technology (C-WET), Chennai in the year 2011 to set up 51 Solar Radiation Resource Assessment (SRRA) stations using the state-of-the-art equipment in various parts of the country, especially the sites with high potential for solar power. The GoI project has synergy with SolMap project, which is implemented by the Deutsche GesellschaftfürInternationaleZusammenarbeit (GIZ) in cooperation with the MNRE. SolMap project is contributing to SRRA project in establishing quality checks on the data obtained as per International protocols and helping data processing to generate investment grade data. The paper highlights the details of SRRA stations and an attempt has been made to present some of the important results of quality control and data analysis with respect to GHI and DNI. While our analysis of the data over one year finds that intensity and profile of the insolation are not uniform across the geographic regions, the variability in DNI is particularly high. Strong influence of monsoon is also identified. SRRA infrastructure aims to develop investment grade solar radiation resource information to assist project activities under the National Solar Mission of India.